Injection molding preparation method of in-situ synthesized amorphous composite material

Through the injection molding preparation method of in-situ synthesis amorphous composite materials, combined with powder metallurgy and sintering technology, the uneven distribution and grain boundary problems in the preparation of large-scale complex shapes are solved, and the preparation of materials with excellent performance and complex shapes is achieved.

CN119506646APending Publication Date: 2025-02-25HUNAN INJECTION HIGH-TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411765137.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

It is difficult to effectively prepare large pieces of complex shape amorphous composite materials, especially while ensuring material properties and shape complexity, there are problems of uneven distribution and grain boundaries.

Method used

The injection molding preparation method of in-situ synthetic amorphous composite materials is used, and combined with powder metallurgy technology, sintering principle, injection molding process and thermal isostatic sintering technology, amorphous composite materials with excellent performance and complex shape are prepared.

Benefits of technology

The efficient preparation of large, complex shape amorphous composite materials is achieved, the room temperature plasticity and mechanical properties of the material are improved, and uneven distribution and grain boundary problems are avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005168733310000051
    Figure BDA0005168733310000051
  • Figure BDA0005168733310000052
    Figure BDA0005168733310000052
Patent Text Reader

Abstract

The invention relates to an injection molding preparation method of an in-situ synthesized amorphous composite material. The basic process comprises the steps of feed preparation, injection molding, degreasing and presintering, and hot isostatic pressing sintering. A process method is developed by combining an amorphous material strengthening mechanism, an injection molding process and a hot isostatic pressing sintering technology through a powder metallurgy technology. By means of the method, the amorphous composite material which is complex in shape and excellent in performance can be prepared, and according to the compression performance of the amorphous composite material, the yield strength ranges from 1700 MPa to 1750 MPa, the compressive strength ranges from 1800 MPa to 1850 MPa, and the plastic strain ranges from 5% to 7%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing an amorphous material, in particular to an injection molding preparation method for an amorphous composite material. Background Art

[0002] Amorphous alloys have a unique atomic arrangement, that is, short-range order and long-range disorder. This structure makes them immune to defects such as grain boundaries and dislocations, thus showing better mechanical properties than traditional crystalline alloys, such as high strength, high hardness and large elastic limit. However, at room temperature, the rapid expansion of shear bands during the destruction of amorphous materials makes them almost free of plastic strain (less than 2%), and their large brittleness limits their wider application. In order to overcome this problem, researchers have found that adding reinforcing phases to amorphous alloys can effectively hinder the rapid expansion of shear bands and promote the formation of shear bands in more directions, so that stress is redistributed and the purpose of improving their room temperature plasticity is achieved. There are two ways to add reinforcing phases. One is the external addition method, that is, directly adding the second phase into the amorphous, and the second is the in-situ self-generation method, that is, directly precipitating the second phase from the amorphous. Compared with the first method, the second phase generated by the in-situ self-generation method has a higher interface bonding strength with the matrix, and the performance of the composite material is relatively better. In this field, CuZr-based amorphous composites have attracted extensive attention because they can form a metastable B2-CuZr phase in situ during solidification, and have excellent amorphous forming ability and comprehensive mechanical properties. When subjected to stress, the B2-CuZr phase can undergo a martensitic phase transformation, which not only gives the material excellent room temperature plastic deformation ability, but also brings about a significant work hardening effect. Therefore, CuZr-based amorphous composites have become a hot topic of research. However, the distribution, size, and content of the second phase have a great influence on the performance of the composite material. The uniformly distributed fine second phase can improve the plasticity and toughness of the amorphous material, but if an unevenly distributed coarse second phase is formed, the performance of the material will be deteriorated. The conventional preparation method of CuZr-based amorphous composites is melting and rapid cooling casting. The amorphous composites obtained are affected by the cooling rate. When preparing large amorphous composites, the cooling rate of the core is slow, and the B2-CuZr phase is concentrated, resulting in uneven overall distribution and showing obvious coarse and uneven organization. Literature reports that the distribution of the B2-CuZr phase can be homogenized by adding Ta as a heterogeneous nucleation site, but the problem is that the amount of added Ta particles is limited and their size is relatively large.

[0003] At present, it is very difficult to prepare bulk amorphous alloys because the amorphous forming ability is limited, the cooling rate is high, and the internal cooling speed of large-sized products is slow, which makes it very easy to form a crystalline phase. Therefore, it is extremely difficult to prepare bulk amorphous alloys by traditional methods and then process them into products of certain sizes and complex shapes through mechanical processing.

[0004] Metal Injection Molding (MIM) is a molding technology that mixes metal powder with a binder to make a feed material, then uses a special injection molding device to heat it and inject it into a mold, and then cools it to obtain a green body of a certain shape. The advantage is that it can mold parts with complex shapes and structures in one go, with high raw material utilization, low mass production cost, and high efficiency.

[0005] In the prior art, the patent "2022106563175 Groove needles for warp knitting machines and a method for making groove needles by injection molding process of amorphous alloys" involves an injection molding process, but the injection molding method used is not a traditional injection molding technology. It uses block raw materials, no adhesives, and the injection temperature is high, which places extremely high requirements on equipment. Since the crystallization temperature of amorphous materials is relatively low, it is close to the thermal decomposition temperature of conventional adhesives on the market, so degreasing is also a difficulty. There are currently few reports on the preparation of amorphous materials using metal injection molding methods. In summary, a method for preparing amorphous composite materials with complex shapes is conducive to the promotion and application of amorphous composite materials. Summary of the invention

[0006] In order to solve the problems of the prior art, the present invention provides an injection molding preparation method for in-situ synthesized amorphous composite materials, which comprehensively considers the characteristics and advantages of each adhesive, and combines with injection molding technology and hot isostatic pressing sintering technology to achieve the preparation of complex structure amorphous products.

[0007] In order to achieve the above object, the present invention adopts the following technical solution:

[0008] A preferred solution is an injection molding preparation method for in-situ synthesis of amorphous composite materials, comprising the following steps:

[0009] A. Feed preparation: the amorphous powder and the adhesive are mixed evenly in proportion, and the volume ratio of the total amount of powder to the adhesive is 55-65%:35-45%;

[0010] B. Injection molding: After the feed is made into particles of uniform size, it is injected into the required green body by an injection molding machine, and the injection temperature is 160-170℃;

[0011] C. Degreasing and pre-sintering, removing the binder in the green body, and then pre-sintering to give the green body a certain strength;

[0012] D. Hot isostatic pressing sintering: the pre-sintered blank is placed in a hot isostatic pressing furnace for further densification. The process is: 440-450℃ for 30-60min, 470-480℃ for 2-5min, pressure 150-200Mpa, without a jacket.

[0013] In a preferred embodiment, the amorphous powder has a mass ratio of (Zr 65 Cu 30Al2Sn3) 100-x Y x , the powder oxygen content is ≤0.2%, when the powder oxygen content is <0.1%, x=0.58~0.88%, when the powder oxygen content is 0.1~0.2%, x=0.88%~1.76%, and the powder particle size is not greater than 500 mesh.

[0014] In a preferred embodiment, the adhesive comprises the following components in mass ratio: 55-65% paraffin PA, 10-20% polymethyl methacrylate PMMA, 15-20% polypropylene PP, 1-2% dioctyl isophthalate DOIP, 1-3% stearic acid SA, and 0.5-1% linseed oil FL oil.

[0015] The preferred scheme is that the degreasing method is carried out in two steps. The first step is solvent degreasing, the solvent is dichloromethane or n-heptane, and the degreasing temperature is 30-40°C. The second step is thermal degreasing and pre-sintering. The process is to heat up to 250-260°C at 1-3°C / min, keep warm for 60-90min, then heat up to 330-350°C at 1-3°C / min, keep warm for 100-150min, and finally heat up to 420-430°C at 5-10°C / min, keep warm for 60-90min, and use Ar2 or N2 protection throughout the process.

[0016] In a preferred solution, the prepared composite material has compression properties of yield strength of 1700-1750 MPa, compressive strength of 1800-1850 MPa, and plastic strain of 5-7%.

[0017] Principles and advantages:

[0018] The present invention adopts powder metallurgy technology, integrates the advantages of sintering principle, amorphous material strengthening mechanism, injection molding process and hot isostatic pressing sintering technology, and designs a process method that can prepare amorphous composite materials with excellent performance and complex shapes.

[0019] In the composition design, Sn and Y are added on the basis of Zr, Cu and Al elements. When making powder, Sn dissolves in amorphous liquid and disperses and precipitates in fine Zr5Sn3 phase before B2-CuZr phase. In the subsequent process, it serves as a heterogeneous nucleation point of B2-CuZr phase. Y plays two roles. On the one hand, it combines with oxygen in the melt to form Y2O3 during powder making, removes other oxides in the melt, prevents B2-CuZr phase from adhering to it to form a coarse crystallized phase, improves melt stability, increases crystallization temperature, reduces glass transition temperature, improves amorphous formation ability, and expands sintering range. On the other hand, when the content of Y is slightly greater than the content of O required for purification, Y will exist in the form of nano-atomic clusters later, also serving as a heterogeneous nucleation point of B2-CuZr phase.

[0020] When designing the adhesive, multiple components are selected and mixed according to the characteristics of each adhesive, and the prepared feed has good injection performance and removal performance. Based on the wax base, paraffin is the main component, providing good fluidity, soluble in organic solvents, and can be removed quickly. PMMA and pure PP are the skeleton components after the paraffin is removed, so that the green body has a certain strength after solvent degreasing and neutralization, and maintains the shape of the green body. The decomposition temperature of both is low. The starting temperature of PMMA rapid thermal decomposition is 300℃, and the starting temperature of pure PP rapid thermal decomposition is 200℃, which can be completely decomposed at a lower temperature. DOIP is used as a plasticizer to improve the fluidity of PA, PMMA, and PP, and improve the injection performance of the feed. SA is a dispersant and lubricant, which disperses the powder, reduces the friction between the mold and the feed, and improves the uniformity and injection conditions. Linseed oil can avoid green body cracks through stress relaxation during injection, increase the powder loading, and become liquid / semi-solid under normal conditions, which can improve the fluidity and injection filling of the feed.

[0021] Hot isostatic pressing has high sintering quality. In hot isostatic pressing, a high pressure is applied to the material during the sintering process, which acts evenly on the surface of the material, causing the powder to undergo plastic deformation and diffusion creep, promoting the discharge of pores. Therefore, compared with traditional sintering, the material can be densified at a lower temperature to avoid uncontrolled crystallization of amorphous materials. Sintering is completed in two stages. The first stage is 440-450℃ to complete the densification, and the second stage is 470-480℃ for a short time to maintain heat to promote the dispersion and precipitation of B2-CuZr phase. DETAILED DESCRIPTION

[0022] The method of the present invention is further described below in conjunction with three embodiments.

[0023] Example 1

[0024] An injection molding preparation method for in-situ synthesized amorphous composite materials comprises the following steps:

[0025] A. Feed preparation: the particle size is not more than 500 mesh, the oxygen content is 0.08%, and the mass ratio is (Zr 65 Cu 30 Al2Sn3) 99.2 Y 0.8 The amorphous powder and the adhesive are uniformly mixed in a volume ratio of 63%:37%, and the mass ratio of the adhesive is: 65% paraffin PA, 11% polymethyl methacrylate PMMA, 20% polypropylene PP, 1% dioctyl isophthalate DOIP, 2.5% stearic acid SA, and 0.5% linseed oil FL oil;

[0026] B. Injection molding: After the feed is made into particles of uniform size, it is injected into the required green body by an injection molding machine at an injection temperature of 170°C;

[0027] C. Debinding and pre-sintering. The debinding method is carried out in two steps. The first step is solvent debinding. The solvent is dichloromethane and the debinding temperature is 35°C. The second step is thermal debinding and pre-sintering. The process is to heat up to 250°C at 3°C / min, keep it warm for 90min, then heat up to 340°C at 3°C / min, keep it warm for 120min, and finally heat up to 425°C at 10°C / min, keep it warm for 75min, and Ar2 protection is used throughout the process.

[0028] D. Hot isostatic pressing sintering: the pre-sintered blank is placed in a hot isostatic pressing furnace for further densification. The process is: 445℃ for 45min, 475℃ for 3min, pressure 170Mpa, without a jacket.

[0029] Example 2

[0030] An injection molding preparation method for in-situ synthesized amorphous composite materials comprises the following steps:

[0031] B. Feed preparation: the particle size is not greater than 500 mesh, the oxygen content is 0.15%, and the mass ratio is (Zr 65 Cu 30 Al2Sn3) 98.5 Y 1.5 The amorphous powder and the adhesive are uniformly mixed in a volume ratio of 65%:35%, and the mass ratio of the adhesive is: 60% paraffin PA, 15% polymethyl methacrylate PMMA, 20% polypropylene PP, 1% dioctyl isophthalate DOIP, 3% stearic acid SA, and 1% linseed oil FL oil;

[0032] B. Injection molding: After the feed is made into particles of uniform size, it is injected into the required green body by an injection molding machine at an injection temperature of 165°C;

[0033] C. Debinding and pre-sintering. The debinding method is carried out in two steps. The first step is solvent debinding. The solvent is dichloromethane and the debinding temperature is 35°C. The second step is thermal debinding and pre-sintering. The process is to heat up to 250°C at 3°C / min, keep it warm for 90min, then heat up to 350°C at 3°C / min, keep it warm for 100min, and finally heat up to 430°C at 10°C / min, keep it warm for 60min, and Ar2 protection is used throughout the process.

[0034] D. Hot isostatic pressing sintering: the pre-sintered blank is placed in a hot isostatic pressing furnace for further densification. The process is: 440℃ for 60min, 470℃ for 5min, pressure 200Mpa, without a jacket.

[0035] Example 3

[0036] An injection molding preparation method for in-situ synthesized amorphous composite materials comprises the following steps:

[0037] C. Feed preparation: the particle size is not greater than 500 mesh, the oxygen content is 0.08%, and the mass ratio composition is (Zr 65 Cu 30 Al2Sn3) 99.2 Y 0.8 The amorphous powder and the adhesive are evenly mixed in a volume ratio of 55%:45%, and the mass ratio of the adhesive is: 55% paraffin PA, 20% polymethyl methacrylate PMMA, 20% polypropylene PP, 2% dioctyl isophthalate DOIP, 2% stearic acid SA, and 1% linseed oil FL oil;

[0038] B. Injection molding: After the feed is made into particles of uniform size, it is injected into the required green body by an injection molding machine at an injection temperature of 170°C;

[0039] C. Debinding and pre-sintering. The debinding method is carried out in two steps. The first step is solvent debinding. The solvent is n-heptane and the debinding temperature is 35°C. The second step is thermal debinding and pre-sintering. The process is to heat up to 260°C at 2°C / min, keep it warm for 60min, then heat up to 330°C at 2°C / min, keep it warm for 150min, and finally heat up to 430°C at 5°C / min, keep it warm for 90min, and N2 protection is passed throughout the process.

[0040] D. Hot isostatic pressing sintering: the pre-sintered blank is placed in a hot isostatic pressing furnace for further densification. The process is: 450°C for 60 minutes, 480°C for 2 minutes, pressure 150Mpa, and no jacket.

[0041] Comparative Example 1

[0042] This comparative example adopts the same process steps as Example 1, except that the mass percentage composition of the amorphous powder is different. The results are shown in the following table.

[0043]

[0044] Comparative Example 2

[0045] This comparative example adopts the same process steps as Example 1, except that the powder composition does not contain Sn. The plastic strain is less than 2%.

[0046] Comparative Example 3

[0047] This comparative example adopts the same process steps as Example 1, except that the sintering process is different. The results are shown in the following table.

[0048]

[0049] Comparative Example 4

[0050] This comparative example adopts the same process steps as Example 1, except that the injection temperature is different. The results are shown in the following table.

[0051] Injection temperature / ℃ evaluate 150 Product not filled 190 Black lines on the product surface, adhesive volatilization

[0052] The above-described examples are only preferred implementation methods of the present invention, and therefore cannot be used to limit the scope of implementation of the present invention. Other equivalent changes, modifications, substitutions and combinations made in accordance with the principles and contents of the present invention still fall within the protection scope of the present invention.

Claims

1. A method for preparing an in-situ synthesized amorphous composite material by injection molding, characterized in that it comprises the following steps: A. Feed preparation: Mix the amorphous powder and the binder evenly according to the proportion. The volume ratio of the total amount of powder to the binder is 55~65%:35~45%; B. Injection molding: After the feed is made into particles of uniform size, it is injected into the required green body by an injection molding machine, and the injection temperature is 160~170℃; C. Degreasing and pre-sintering, removing the binder in the green body, and then pre-sintering to give the green body a certain strength; D. Hot isostatic pressing sintering: the pre-sintered blank is placed in a hot isostatic pressing furnace for further densification. The process is: 440~450℃ for 30~60min, 470~480℃ for 2~5min, pressure 150~200Mpa, without a jacket.

2. The injection molding preparation method according to claim 1, characterized in that: The mass ratio of amorphous powder is (Zr 65 Cu 30 Al2Sn3) 100-x Y x , the powder oxygen content is ≤0.2%, when the powder oxygen content is <0.1%, x=0.58~0.88%, when the powder oxygen content is 0.1~0.2%, x=0.88%~1.76%, the powder particle size is not greater than 500 mesh.

3. The injection molding preparation method according to claim 1, characterized in that: The adhesive comprises: 55-65% paraffin PA, 10-20% polymethyl methacrylate PMMA, 15-20% polypropylene PP, 1-2% dioctyl isophthalate DOIP, 1-3% stearic acid SA, and 0.5-1% linseed oil FL oil by mass ratio.

4. The injection molding preparation method according to claim 1, characterized in that: The degreasing method is carried out in two steps. The first step is solvent degreasing, the solvent is dichloromethane or n-heptane, and the degreasing temperature is 30-40°C. The second step is thermal degreasing and pre-sintering. The process is to heat up to 250-260°C at 1-3°C / min, keep warm for 60-90min, then heat up to 330-350°C at 1-3°C / min, keep warm for 100-150min, and finally heat up to 420-430°C at 5-10°C / min, keep warm for 60-90min, and use Ar2 or N2 protection throughout the process.

5. The injection molding preparation method according to claim 1, characterized in that: The compression properties of the prepared composite material are yield strength 1700~1750MPa, compressive strength 1800~1850MPa, and plastic strain 5~7%.